2014
DOI: 10.1634/theoncologist.2014-0135
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profiles in the Management of Papillary Thyroid Cancer

Abstract: Papillary thyroid cancer (PTC) is the major contributor to the dramatically increasing incidence of thyroid cancer. Low-risk PTC shows the most rapid rate of increase because of changing trends in neck imaging and the use of fine needle aspiration to investigate thyroid nodules. The need for a paradigm shift in the management of these patients, to provide personalized treatment and surveillance plans, has led to the focus on molecular biomarker research. MicroRNAs (miRNAs) compose a class of molecules with pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 54 publications
1
35
0
1
Order By: Relevance
“…miRNAs serve important roles in the formation and progression of PTC by regulating numerous physiological and pathological behaviours (24,25). Hence, investigating the functional roles of specific miRNAs in PTC may contribute in identifying effective therapeutic targets for the management of patients with PTC.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs serve important roles in the formation and progression of PTC by regulating numerous physiological and pathological behaviours (24,25). Hence, investigating the functional roles of specific miRNAs in PTC may contribute in identifying effective therapeutic targets for the management of patients with PTC.…”
Section: Discussionmentioning
confidence: 99%
“…9 It is reported that miRNAs were involved in every stage of PTC, including tumor diagnosis, prognosis, treatment and surveillance. 10 According to the small RNA deep-sequencing data, miR-873-5p expression in PTC is downregulated in tumors compared to normal samples. 11 However, the roles of miR-873-5p in PTC and the underlying molecular mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that miRNAs are aberrantly expressed in almost all types of human cancer, including PTC (12), colorectal cancer (13), lung cancer (14), glioblastoma (15) MicroRNA-766 inhibits papillary thyroid cancer progression by directly targeting insulin receptor substrate 2 and regulating the PI3K/Akt pathway and bladder cancer (16). Increasing evidence has revealed that various miRNAs are differentially expressed in PTC, and their dysregulation has been implicated in the regulation of PTC occurrence and development (17)(18)(19). Furthermore, miRNAs may have tumor suppressive or oncogenic roles in the progression of PTC and are able to regulate various cancer-associated biological processes, including cell proliferation, cell cycle progression, apoptosis, invasion, metastasis and epithelial-mesenchymal transition (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%